Kajian Etnobiologi pada Makanan Khas Suku Karo di Kecamatan Sibiru-biru Kabupaten Deli Serdang - Maria Goreti Perawati Br. Manik; Dina Handayani (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to document and analyze the traditional food of the Karo Tribe in the seven-monthly ceremony (Mbesur-mbesuri) in the Karo Tribe community in Sibiru-biru District, Deli Serdang Regency. This study was conducted in two villages, namely Biru-biru Village and Rumah Gerat Village, Sibiru-biru District, Deli Serdang Regency. This type of research is descriptive qualitative and quantitative using emic and etic research approaches. Data collection techniques were carried out by participatory observation, interview techniques, documentation techniques, Focus Group Discussions (FGD), plant identification, and animal identification. The results of the study show that the traditional food of the Karo Tribe contained in the seven-monthly ceremony (Mbesur-mbesuri) consists of seven types of mandatory foods that utilize 19 types of plants belonging to 12 families, and 1 type of animal from the Phasianida family. The dominant plant family used in the traditional food of the seven-monthly ceremony (Mbesur-mbesuri) is Zingiberaceae. The most frequently used part of the plant is the fruit, namely 6 types. In terms of plant habitus, herbs are the most dominant species used in the seven-monthly ceremony (Mbesur-mbesuri), with 13 species.